An extension of the Beretta-Kuang model of viral diseases - Ivo Siekmann; Horst Malchow; Ezio Venturino (Mathematical Biosciences and Engineering)
A model for the complete life cycle of marine viruses is presented.The Beretta-Kuang model introduces an explicit equation for viral particlesbut the replication process of viral particles in their hosts is not considered.The extended model keeps the structure of the original model. This makes itpossible to estimate the growth parameters of the viruses for a given parametrisationof the Beretta-Kuang model.